The Problematic Genus Sclerocardius (Coleoptera: Curculionidae: Molytinae: Ithyporini) - Christopher H. C. Lyal (Diversity, 2018)
The genus Sclerocardius is revised, using morphological characters. Four species are recognized, including S. africanus (Boheman), S. bohemani Schoenherr stat.rev., S. indicus Hartmann and S. kuscheli sp.nov. The species Sclerocardius madecassus Ferragu is synonymized with S. bohemani syn.nov., and Charactocnemus hintzi Hartmann is treated as a junior synonym of S. bohemani, not S. africanus. A key to species is given. Lectotypes are designated for Heteramphus africanus Boheman and Sclerocardius africanus Schoenherr. A female elytro-tergal stridulatory system involving the modification of the wing-binding patch of the seventh tergite is reported for the Sclerocardiina for the first time and supports the inclusion of the subtribe within the Ithyporini.